Role of clinical examination, ultrasound findings and serum beta-hCG in first trimester vaginal bleeding - Lalchand, Hemapriya; Doddapaneni, Praharshita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: The significance of bleeding in first trimester of pregnancy may vary from an inconsequential episode to a life-threatening emergency. USG is safe and non-invasive and widely used for diagnosis various problems in pregnancy. Beta hCG can be detected in the plasma of a pregnant woman as early as eight days after ovulation, and its quantitative estimation can provide useful information regarding early pregnancy. Aim was to determine the role of clinical examination, ultrasonographic parameters and serum beta-hCG in predicting the outcome of pregnancy in first trimester vaginal bleeding. Methods: It was a prospective observational study conducted in the department of OBG at JSS medical college, Mysuru for a duration of 18 months where in, serum beta-hCG levels, ultrasound examination was done in 120 patients presenting with first trimester of vaginal bleeding with gestational age less than 13 weeks. Results: Out of 120 patients in our study, 39 patients had miscarriage and 81 patients had viable pregnancy at 28 weeks of gestation. Among those who had pregnancy loss, higher beta-hCG levels were found at 6-8 weeks of gestation. Higher incidence of miscarriage was found in association with subchorionic haemorrhage and smaller gestational sac. No statistically significant association between the pregnancy loss and ultrasound parameters was noted in our study. Conclusions: The incidence of miscarriage in our study was 32.5%. No statistically significant association between the biochemical and ultrasonography parameters with pregnancy loss in patients presenting with threatened abortion could be established in our study.